Characterization of strain-softening behavior and failure mechanisms of composites under tension and compression. (January 2015) - Zobeiry, N.; Vaziri, R.; Poursartip, A.
Abstract: A methodology is presented to directly measure the damage properties and strain softening response of laminated composites by conducting over-height compact tension (OCT) and compact compression (CC) tests. Through the use of digital image correlation (DIC) technique, and analysis of the measured surface displacement/strain data, the strain-softening response of composites is constructed. This method leads to a direct determination of the Mode I translaminar fracture properties with the assumption that the shear stress is negligible around the damage zone and the crack growth occurs in the symmetric opening mode. Using this methodology, and by correlating the observed failure mechanisms with the strain-softening curves, the interaction of failure mechanisms leading to the final failure and also the distinction between the tensile and compressive failure mechanisms can be studied. The effectiveness of the method in accurate identification of the damage parameters is demonstrated through sectioning and deplying techniques. As a consistency check and further verification of the method, the obtained strain-softening curves are fed into a numerical damage mechanics model and successfully used to simulate the detailed response of the very same OCT and CC specimens from which the strain-softening curves were extracted.